Evaluation of CDMA2000 support for IP micromobility handover andpaging protocols. - Sarikaya, B. (IEEE Communications magazine)
Research in Mobile IP has proposed that IP should take support from the underlying wireless network architecture to achieve good performance for handover and paging protocols. The IETF work defines requirements for layer 2 (the data link layer of the OSI model) to support optimized layer 3 (the network layer of the OSI model) handover and paging protocols. Layer 2 can send notification to layer 3 that a certain event has happened or is about to happen. The notification is sent using a trigger. We list the triggers needed by IP handover and paging protocols. We map the triggers to their corresponding events in CDMA2000